2016
DOI: 10.1371/journal.pone.0165041
|View full text |Cite
|
Sign up to set email alerts
|

Association between Social Network Characteristics and Lifestyle Behaviours in Adults at Risk of Diabetes and Cardiovascular Disease

Abstract: ObjectivesIn this exploratory study we examined the associations between several social network characteristics and lifestyle behaviours in adults at increased risk of diabetes and cardiovascular diseases. In addition, we explored whether similarities in lifestyle between individuals and their network members, or the level of social support perceived by these individuals, could explain these associations.MethodsFrom the control group of the Hoorn Prevention Study, participants with high and low educational att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Our findings are consistent with previous, mainly cross-sectional studies on the association between social networks and health risk behaviours [12,13,[15][16][17]20,[32][33][34]. Previous studies have shown, for example, that individuals who drink heavily report decreased levels of social activities, worse social anchorage and low contact frequency [32].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with previous, mainly cross-sectional studies on the association between social networks and health risk behaviours [12,13,[15][16][17]20,[32][33][34]. Previous studies have shown, for example, that individuals who drink heavily report decreased levels of social activities, worse social anchorage and low contact frequency [32].…”
Section: Discussionsupporting
confidence: 92%
“…An association with physical inactivity has previously been reported for various measures of low social engagement, such as low social integration and a small number of friends and close network members [12,13,16,17,20]. Similarly, our results highlight the importance of social network size on physical activity, the strongest and most robust association observed in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, there may be more societally-related factors that may impact a person's health-related behavior besides high self-efficacy and the ability to make plans. For example, Bot et al [32] examined the impact of lifestyle behaviors and social networking on health outcomes in a sample of 50 participants at risk for cardiovascular or metabolic conditions, and 170 members of their social circles. The investigators concluded that those with close and densely packed relational circles were found to be more physically active.…”
Section: Discussionmentioning
confidence: 99%
“…Social relations may increase the level of physical activity, and the consumption of fruit and vegetables [9]. Bot et al suggest that the elderly living in a larger and denser social network have a healthier lifestyle [10]. Dickens et al, in a systematic review, have indicated that the activities carried out in groups counteract social exclusion [11], which is closely linked with an increased risk of limiting functional autonomy [12] and death [13].…”
Section: Introductionmentioning
confidence: 99%